A conceptual approach to graphically compare construction schedules. Issue 1 (6th January 2020) - Hatipkarasulu, Yilmaz
Abstract : Purpose: This paper aims to present a graphical comparison method for construction schedules, which illustrates the differences for each individual activity. The method overlays the observed differences on a bar chart creating a representation of whether each activity is ahead, on or behind schedule at a given date. Design/methodology/approach: The method is implemented using a Microsoft Project add-in (plug-in). The paper demonstrates the method and its potential uses with three illustration cases: a time impact analysis, an alternative analysis for the selection of subcontractors and a multi-baseline analysis of an as-built schedule. Findings: The cases included in the paper show that the proposed method uses a simplified and familiar attribute comparison for each activity in a schedule. The method affords flexibility in presenting differences between schedules such as the start/finish dates or duration. As the method does not rely on a specific software application or analysis method, it can be implement to different software applications as well as performance or delay analysis techniques. The method also makes it possible to present multiple and selective baseline comparisons overlaid on an updated or as-built schedule. Originality/value: The method graphically presents a comparison of start dates, durations and finish dates for each activity that can be integrated with any schedule. The method can be used for forensic analysis as well as project control measures during construction. As the method does not rely on any specific performance or delay calculation method, it can be applied to any forensic analysis technique and delay analysis.